Fusion reaction dynamics of fullerene molecules. (July 2015) - Wang, Yang; Gatchell, Michael; Zettergren, Henning; Rousseau, Patrick; Chen, Tao; Stockett, Mark H; Domaracka, Alicja; Adoui, Lamri; Huber, Bernd A; Cederquist, Henrik; Alcamí, Manuel; Martín, Fernando
Synopsis: Systematic molecular dynamics simulations based on the self-consistent charge density functional tight-binding method have been performed for the molecular collisions inside clusters of fullerene molecules, after prompt atom knockouts by the keV ions. The thermodynamic and kinetic stabilities, as well as the bonding features, have been investigated for the most stable dumbbell dimers C + 18, C + 19 and C + 20 .